Allusion to the poets - Ricks, Christopher B. (Oxford University Press, 2002)
Allusion to the words and phrases of ancestral voices is one of the hiding-places of poetry's power. Poets appreciate the great debts that they owe to previous poets, and are often duly and newly grateful. Allusion to the Poets consists of twelve essays - four published here for the first time - on allusion and its relations, in particular on the use that poets in English have made of the very words of poets in English. The first half of the book, on 'The Poet as Heir', consists of six chapters devoted to individual poets, Augustan, Romantic, and Victorian: Dryden and Pope, Burns, Wordsworth, Byron, Keats, and Tennyson. Allusion is always a form of inheritance, not to be hoarded or squandered. The critical and creative question is its imaginative co-operation with other kinds of legacy - with whatever for a particular poet or for a particular time is judged to be an unignorable inheritance: of a throne, perhaps, or of land; of intermixed languages; of the human senses; of money; of literature itself; or of our planet, long-lived but not eternal.; The second half of the book is six essays on allusion's affiliations: to plagiarism (allusion being plagiarism's responsible opposite); to metaphor (allusion being a form that metaphor may take); to loneliness in poetry (allusion constituting company). And on allusion within poetry to prose (A E. Housman); on translation as exercising allusion (David Ferry); and on the clash between one poet's practice and his critical principles (Yvor Winters).